Intracranial bony ball - An ossified variant of meningioma - Gayathri Priyadharshini; Manjiri Phansalkar; Dilip Phansalkar; Vellore Seetharam Hari (Wolters Kluwer Medknow Publications, 2020)
An ossified variant of meningioma in the intracranial region is very rare. We report a case of a 28-year-old female who presented with headache for 4 years. Imaging revealed an extra-axial calcified mass in the left parieto-occipital lobe. The differential diagnosis included osteoblastoma both intracranial and periosteal, calcifying pseudotumor of the neural axis, hyperostosis of the cranium, and ossifying fibroma. She underwent excision of the calcified space occupying lesion. Histopathology was suggestive of an ossified meningioma. At the end of 2-year follow-up, she was asymptomatic with no signs of recurrence.